Investigating Human Factors in Biotechnology and Pharmaceutical Manufacturing industries - CORRIGAN, SIOBHAN (My University, 2011)
The aim of this paper is to present the work carried out in a European Commission-funded project to adapt an existing Aircraft Maintenance Human Factors (HF) training program (STAMINA) to the Biotechnology and Pharmaceutical Manufacturing industries (BPM). The STAMINA approach has been successfully built into a global human factors training business recognized internationally as a quality benchmark. The Biotechnology and Pharmaceutical Industries have a similar need for human factors training, but with a less elaborated research and regulatory framework. The goal of the project is to provide training to increase and support operational safety, product quality and process reliability within the BPM industry. This paper presents the findings from the first two stages of the project: (a) literature review and (b) research findings.
PUBLISHED
Keywords: Psychology; operational safety; Pharmaceutical and Biotechnology manufacturing